2018
DOI: 10.1101/268011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elevated temperature increases genome-wide selection on de novo mutations

Abstract: Adaptation in new environments depends on the amount and type of genetic variation available for evolution, and the efficacy by which natural selection discriminates among this variation to favour the survival of the fittest. However, whether some environments systematically reveal more genetic variation in fitness, or impose stronger selection pressures than others, is typically not known. Here, we apply enzyme kinetic theory to show that rising global temperatures are predicted to intensify natural selection… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 83 publications
0
28
1
3
Order By: Relevance
“…Of those stresses that were found to significantly affect the strength of selection, 12 strengthened selection, whereas 10 weakened selection. In another recent analysis of existing data, Berger et al (2018) also found no evidence that stress increases the severity of mutational load, though this study does suggest that temperature specifically may exaggerate mutational effects. Therefore, with the exception of population density, there is still little evidence that environmental stress increases the strength of selection, although the common intuition that it does continues to be repeated (e.g.…”
Section: Introductioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Of those stresses that were found to significantly affect the strength of selection, 12 strengthened selection, whereas 10 weakened selection. In another recent analysis of existing data, Berger et al (2018) also found no evidence that stress increases the severity of mutational load, though this study does suggest that temperature specifically may exaggerate mutational effects. Therefore, with the exception of population density, there is still little evidence that environmental stress increases the strength of selection, although the common intuition that it does continues to be repeated (e.g.…”
Section: Introductioncontrasting
confidence: 85%
“…Our finding of no relationship between stress and selection is in accord with the consensus from previous studies; reviews and comprehensive studies have found that environmental stress can strengthen, weaken or have no effect on selection, with no clear trend (Table , Martin & Lenormand, ; Agrawal & Whitlock, ; Yun & Agrawal, ; Berger et al ., ). There is an exception for the environmental stress of high population density, which consistently increases selection strength in past studies (Agrawal & Whitlock, ; Yun & Agrawal, ).…”
Section: Discussionmentioning
confidence: 97%
“…The ability of an organism to undergo rapid adaptation to novel ecological conditions such as elevated temperature is reliant on the existence of standing genetic variation within a population (Davis & Shaw, 2001;Orr & Betancourt, 2001;Blows & Hoffmann, 2005;Willi et al, 2006;Berger et al, 2020). Therefore, a reduction in genetic diversity could restrict the evolvability of populations to environmental stochasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, a recent study has shown that increasing temperature results in significantly more genome-wide de novo mutations (Berger et al, 2020). However, empirical support for a corresponding increase in inbreeding depression owing to the accumulation of these thermal stress-induced mutations is varied.…”
Section: Introductionmentioning
confidence: 99%
“…to be exclusively driven by the decline in protein stability at high temperatures (Puurtinen et al 2016;Berger et al 2020;Figure 1A). Under this hypothesis, ΔΔ is assumed to be independent of temperature and constant (the "temperature-invariant ΔΔ " hypothesis).…”
Section: Introductionmentioning
confidence: 99%